The role of childhood trauma in affective stress recovery in early psychosis: an experience sampling study - Ader, Leonie; Schick, Anita; Vaessen, Thomas; Alizadeh, Behrooz Z; van Amelsvoort, Therese; Cahn, Wiepke; de Haan, Lieuwe; Schirmbeck, Frederike; Simons, Claudia J P; van Os, Jim; Veling, Wim; Morgan, Craig; et al. (Schizophrenia bulletin, 2024)
Abstract - Background and Hypotheses: Affective recovery, operationalized as the time needed for affect to return to baseline levels after daily stressors, may be a putative momentary representation of resilience. This study aimed to investigate affective recovery in positive and negative affect across subclinical and clinical stages of psychosis and whether this is associated with exposure to childhood trauma (sexual, physical, and emotional abuse). Study Design: We used survival analysis to predict the time-to-recovery from a daily event-related stressor in a pooled sample of 3 previously conducted experience sampling studies including 113 individuals with first-episode psychosis, 162 at-risk individuals, and 94 controls. Study Results: Negative affective recovery (ie, return to baseline following an increase in negative affect) was longer in individuals with first-episode psychosis compared with controls (hazard ratio [HR] = 1.71, 95% confidence interval [CI; 1.03, 2.61], P = .04) and in at-risk individuals exposed to high vs low levels of emotional abuse (HR = 1.31, 95% CI [1.06, 1.62], P = .01). Positive affective recovery (ie, return to baseline following a decrease in positive affect) did not differ between groups and was not associated with childhood trauma. Conclusions: Our results give first indications that negative affective recovery may be a putative momentary representation of resilience across stages of psychosis and may be amplified in at-risk individuals with prior experiences of emotional abuse. Understanding how affective recovery contributes to the development of psychosis may help identify new targets for prevention and intervention to buffer risk or foster resilience in daily life.
Gesehen am 09.09.2024